Hubungan pengetahuan dengan upaya pencegahan kekambuhan hipertensi pada lansia - Fauzhan, Fathan; tresnawan, Teten; Lidyawati, Herlina (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Hypertension is a chronic non-communicable disease characterized by systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg, and is a leading cause of premature death globally, with a prevalence of more than 1.13 billion people. Objective: To determine the relationship between knowledge and efforts to prevent hypertension recurrence among elderly in Selabatu Village. Methods: This was a quantitative analytical correlational study with a cross-sectional design. The population consisted of 877 elderly with hypertension, with a sample of 90 respondents selected using stratified random sampling. Instruments were a knowledge questionnaire (15 items, Likert scale, α=0.85) and a prevention effort questionnaire (15 items, positive/negative Likert items, α>0.7), both valid and reliable. Bivariate analysis used the Chi-Square test. Results: Based on the study results, the level of knowledge among hypertension sufferers, with a total sample of 90 respondents, was found to be quite good (42 respondents (46.7%). The results of hypertension prevention efforts were also found to be quite good (36 respondents (40.0%). The chi-square statistical test yielded a P-value of 0.001 < 0.05. Conclusion: There is a relationship between knowledge and hypertension prevention efforts in the elderly. Keywords: Elderly; Hypertension; Knowledge; Recurrence Prevention. Pendahuluan: Hipertensi merupakan penyakit tidak menular kronis dengan tekanan darah sistolik ≥140 mmHg atau diastolik ≥90 mmHg, yang menjadi penyebab utama kematian dini global dengan prevalensi >1.13 miliar orang. Tujuan: Untuk mengetahui hubungan pengetahuan dengan upaya pencegahan kekambuhan hipertensi pada lansia. Metode: Penelitian kuantitatif analitik korelasional dengan desain cross-sectional. Populasi 877 lansia hipertensi, sampel 90 responden via stratified random sampling. Instrumen: kuesioner pengetahuan (15 item, Likert, α=0.85) dan upaya pencegahan (15 item, Likert positif/negatif, α>0.7), valid dan reliabel. Analisis bivariat menggunakan Chi-Square.​ Hasil: Berdasarkan hasil penelitian di dapatkan tingkat pengetahuan pada penderita hipertensi dengan total sampel 90 responden, hampir setengahnya dalam kategori cukup baik sebanyak 42 responden (46.7%). Hasil upaya pencegahan hipertensi hampir setengahnya dalam kategori cukup baik sebanyak 36 responden (40,0%). Hasil uji statistik dengan chi-square nilai P yang dihasilkan sebesar 0.001 < 0.05. Simpulan: Ada hubungan pengetahuan dengan upaya pencegahan hipertensi pada lansia. Kata Kunci: Hipertensi; Lansia; Pengetahuan; Pencegahan Kekambuhan.